High-Resolution Landmark Framework for the Sequence-Ready Mapping of Xq23–q26.1 - Steingruber, Helen E.; Dunham, Andrew; Coffey, Alison J.; Clegg, Sheila M.; Howell, Gareth R.; Maslen, Gareth L.; Scott, Carol E.; Gwilliam, Rhian; Hunt, Paul J.; Sotheran, Elizabeth C.; Huckle, Elizabeth J.; Hunt, Sarah E.; et al.

(untitled) (Genome Research, 1999)
We have established a landmark framework map over 20–25 Mb of the long arm of the human X chromosome using yeast artificial chromosome (YAC) clones. The map has approximately one landmark per 45 kb of DNA and stretches from DXS7531 in proximal Xq23 to DXS895 in proximal Xq26, connecting to published framework maps on its proximal and distal sides. There are three gaps in the framework map resulting from the failure to obtain clone coverage from the YAC resources available. Estimates of the maximum sizes of these gaps have been obtained. The four YAC contigs have been positioned and oriented using somatic-cell hybrids and fluorescence in situ hybridization, and the largest is estimated to cover ∼15 Mb of DNA. The framework map is being used to assemble a sequence-ready map in large-insert bacterial clones, as part of an international effort to complete the sequence of the X chromosome. PAC and BAC contigs currently cover 18 Mb of the region, and from these, 12 Mb of finished sequence is available.